Phytoplankton composition of Unimas lake in east campus, Sarawak - Fizawati, Binti Kamis (Universiti Malaysia Sarawak, UNIMAS, 2012)
A study on the phytoplankton composition in man-made lake was conducted at two lakes in East Campus of Universiti Malaysia Sarawak, Kota Samarahan. Sampling of phytoplankton from two of the lakes, were conducted from October 2011 until April 2012. Three stations were established at different parts of each lake, namely the inflow, middle and outflow of the lakes. Results showed that the phytoplankton biomass (chlorophyll a) in the lakes were negatively correlated with pH and dissolved oxygen (DO) but positively correlated with nitrate (NO3 - -). A total of 5 algal classes were identified, which was dominated by members from the Chlorophyceae (13 genera), followed by Bacillariophyceae (10 genera), Cyanophyceae (6 genera), Euglenophyceae (3 genera) and Dinophyceae (1 genera). During the study period, water temperature recorded was in the range of 27.45C – 30.87C, with pH from 6.26 – 7.60. Dissolved oxygen varied from 1.07 mg/L – 6.14 mg/L with concentration of nitrate (NO3 - -) and orthophosphate (PO4 3- -) ranged from 0.01 mg/L – 0.09 mg/L and 0.05 mg/L – 0.23 mg/L respectively.